Immobilization of Pseudorabies Virus in Porcine Tracheal Respiratory Mucus Revealed by Single Particle Tracking - Yang, Xiaoyun (Public Library of Science, 2012)
Pseudorabies virus (PRV) initially replicates in the porcine upper respiratory tract. It easily invades the mucosae and submucosae for subsequent spread throughout the body via blood vessels and nervous system. In this context, PRV developed ingenious processes to overcome different barriers such as epithelial cells and the basement membrane. Another important but often overlooked barrier is the substantial mucus layer which coats the mucosae. However, little is known about how PRV particles interact with porcine respiratory mucus. We therefore measured the barrier properties of porcine tracheal respiratory mucus, and investigated the mobility of nanoparticles including PRV in this mucus. We developed an in vitro model utilizing single particle tracking microscopy. Firstly, the mucus pore size was evaluated with polyethylene glycol coupled (PEGylated) nanoparticles and atomic force microscope. Secondly, the mobility of PRV in porcine tracheal respiratory mucus was examined and compared with that of negative, positive and PEGylated nanoparticles. The pore size of porcine tracheal respiratory mucus ranged from 80 to 1500 nm, with an average diameter of 455±240 nm. PRV (zeta potential: −31.8±1.5 mV) experienced a severe obstruction in porcine tracheal respiratory mucus, diffusing 59-fold more slowly than in water. Similarly, the highly negatively (−49.8±0.6 mV) and positively (36.7±1.1 mV) charged nanoparticles were significantly trapped. In contrast, the nearly neutral, hydrophilic PEGylated nanoparticles (−9.6±0.8 mV) diffused rapidly, with the majority of particles moving 50-fold faster than PRV. The mobility of the particles measured was found to be related but not correlated to their surface charge. Furthermore, PEGylated PRV (-13.8±0.9 mV) was observed to diffuse 13-fold faster than native PRV. These findings clearly show that the mobility of PRV was significantly hindered in porcine tracheal respiratory mucus, and that the obstruction of PRV was due to complex mucoadhesive interactions including charge interactions rather than size exclusion.